DAMPAK WORD OF MOUTH, MEDIA SOSIAL, DAN PERSEPSI KUALITAS LAYANAN TERHADAP CUSTOMER SATIFACTION DI RESTORAN AYAM BAKAR POJOK KANWA - Anniza Rochzana; Jessica Abigail; Irra Chrisyanti Dewi (ITB AAS Indonesia Surakarta, 2026)
This research intends to examine the effect of word of mouth (WOM), social media, and perceived service quality on customer satisfaction at Ayam Bakar Pojok Kanwa Restaurant. The study is based on the increasingly competitive food and beverage industry, which requires restaurants to combine effective communication strategies with satisfying service experiences. This study adopted a quantitative research design by collecting data through questionnaires administered to 226 respondents who had previously visited the restaurant. Multiple linear regression was employed to analyze the data. The findings indicate that word of mouth as well as perceived service quality demonstrate a significant impact on customer satisfaction, while social media does not have a significant effect. Collectively, all three variables influence customer satisfaction, with an R² value of 40.4%. Among the independent variables, perceived service quality is the dominant factor. These results indicate that improving service quality and promoting positive customer recommendations are essential strategies for enhancing customer satisfaction as well as strengthening customer loyalty within the restaurant sector. Keywords: WoM, social media, perceived service quality, customer satisfaction.